Electrochemistry inside microdroplets of kerosene: Electroanalysis of (methylcyclopentadienyl) manganese(I) tricarbonyl(I) - Munoz, R; Banks, C; Davies, T; Angnes, L; Compton, R (2006)
A novel electrochemical technique for the determination of (methycyclopentadienyl) manganese(I) tricarbonyl in kerosene is presented. The protocol involves creating an ensemble of microdroplets via spraying a fine mist of the sample under investigation onto an electrode substrate which is then immersed into an immiscible supported phase of either water or acetonitrile which can be used to voltammetrically interrogate the species of interest. In particular the kerosene | acetonitrile interface allows the study of the electrochemical oxidation of (methycyclopentadienyl) manganese(I) tricarbonyl, MMT which normally occurs at large overpotentials (E1/2 = + 1.22 V vs. saturated calomel electrode). Proof-of-concept is shown for kerosene droplets containing MMT suggesting a generic methodology for the electrochemical determination of analytes in voltammetrically otherwise inaccessible media such as petroleum and oils. © 2006 Wiley-VCH Verlag GmbH and Co. KGaA.